2020
DOI: 10.1038/s41598-020-66200-9
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin D binds to the acidic C-terminus region of α-Synuclein and affects its aggregation characteristics

Abstract: cyclophilin D (cypD) is a peptidyl-prolyl isomerase expressed in the nucleus and transported into the mitochondria where it is best associated with the regulation of the mitochondrial permeability transition pore (Mptp). there are, however, other possible roles of cypD in the mitochondria which may or may not be linked with the Mptp. Alpha synuclein (αSyn) is shown here to interact directly with cypD via its acidic proline-rich c-terminus region and binding at the putative ligand binding pocket of cypD. the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In order to gain further insights into the PPIA/tau interaction, we titrated 15 N-labeled PPIA with unlabeled tau. Only at very high molar excess of tau over PPIA did we detect Concentration of PPIA inside tau droplets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to gain further insights into the PPIA/tau interaction, we titrated 15 N-labeled PPIA with unlabeled tau. Only at very high molar excess of tau over PPIA did we detect Concentration of PPIA inside tau droplets.…”
Section: Resultsmentioning
confidence: 99%
“…Peptidyl prolyl isomerases are cotranslational chaperones that assist in the folding of nascent amino acid chains. Their chaperoning activity in protein folding is associated with the cis/trans-interconversion of prolines, the only amino acid that can exist in both conformations. ,, Apart from their function in protein folding, prolyl isomerases, through the combination of their binding and isomerase activity, are associated with higher order assembly formation of IDPs, particularly the disease-associated misfolding of IDPs into amyloid fibrils: prolyl isomerases such as FK506-binding proteins, cyclophilin A, and cyclophilin D modulate the amyloid fibril formation of proline-rich IDPs associated with neurodegeneration including tau and α-synuclein. In contrast to the regulatory activity of prolyl isomerases on the fibril formation of IDPs, their regulatory role on the LLPS behavior of IDPs is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…CypD then remained the only protein whose involvement in the mPTP was uncontested: experiments performed with transgenic mice lacking the peptidylprolyl isomerase f (Ppif ) gene confirmed that this protein is a key element of the mPTP that is responsible for its sensitivity to Cyclosporin A (Basso et al, 2005;Valasani et al, 2014Valasani et al, , 2016Lindblom et al, 2020;Torpey et al, 2020;Panel et al, 2021). However, it should be stressed that CypD plays a regulatory role and is not involved in the pore itself (Fayaz, Raj & Krishnamurthy, 2015).…”
Section: From the Initial Observations To The Composition And Regulation Of The Permeability Transition: An Evolving Modelmentioning
confidence: 99%
“…Owing to its higher proportion of charged residues and low hydrophobicity, it is conceivable that this domain undergoes specific phosphorylation at discrete sites [ 188 , 189 ] and is responsible for the intrinsically unstructured topology of α-synuclein. As radical as it may seem, there is now compelling evidence that the obliteration of C terminus, in tandem with alterations to the domain hydrophobicity, may possibly compromise the membrane-binding machinery and enhance the aggregation propensity of α-synuclein [ 190 195 ].…”
Section: The α-Synuclein Architecturementioning
confidence: 99%